Assessing Functional Safety Parameters with Respect to a Safety Application - Srinivasan Srikanth Kaniyanoor, R Prashanth Gadila, Rangaiha L (International Journal of Advanced Science and Technology, 2020)
The common problem faced by Tier 1 and Tier2 customers is to supply products to customers with different market segments having different safety integrity level requirements. Developing a system with the highest integrity level will directly reflect on the cost of the product and an increased cycle time making it not viable for Tier1 / Tier2 vendors to sell their products. Further executing all the safety mechanisms will reduce the bandwidth for the customers to execute their workloads. In order to meet the varying customer demands, it is preferable to have configurable safety mechanisms which can be enabled or disabled as a function of process safety time, proof test interval time and achieve an optimal tradeoff to meet the required diagnostic coverage without compromising the target safety integrity level.